The road to durable democracy: dominant party regimes, party politics and democratic survival. Issue 8 (17th November 2022) - Yan, Huang-Ting
ABSTRACT: This study examines why regime survival rates vary across young democracies. The author argues that there is a relationship between the type of authoritarian regime and the survival of subsequent democracies. Old regime elites inherit valuable resources from former dominant party regimes that may increase the likelihood of authoritarian successor parties (ASPs) performing well under democracy. This, in turn, for one thing, reduces the fragmentation of the new ruling parties, which inoculates young democracies against political instability that could lead to regime collapse. For another, it can effectively check the government's power, thus preventing a new ruling party from crossing the line from democracy to authoritarianism. This study considers the hypothesis that dominant party regimes have a positive impact on the electoral performance of ASPs under democracy, thus contributing to the longevity of democracies, and tests that hypothesis by combining quantitative and qualitative analysis.